Bacteria and virulence factors in periapical lesions associated with teeth following primary and secondary root canal treatment. (28th December 2020) - Bronzato, J. D.; Davidian, M. E. S.; de Castro, M.; de‐Jesus‐Soares, A.; Ferraz, C. C. R.; Almeida, J. F. A.; Marciano, M. A.; Gomes, B. P. F. A.
Abstract: Aim: This cross‐sectional study aimed to investigate the microbial profile and to quantify the levels of endotoxins (LPS) and lipoteichoic acid (LTA) present in periapical lesions associated with root filled teeth and those that had received root canal retreatment. It also aimed to investigate the association between microorganisms and their virulence factors with clinical and radiographic features. Methodology: Patients with periapical lesions in teeth with post‐treatment endodontic disease following primary root canal treatment ( n  = 19) and unsuccessful root canal retreatment ( n  = 13) were treatment planned for endodontic microsurgery, where the periapical lesions were collected. Clinical and radiographic data were also collected. For microbiological analysis, nested polymerase chain reaction was used to detect 17 bacterial species. Levels of LPS and LTA were determined using limulus amebocyte lysate and enzyme‐linked immunosorbent assays, respectively. The Student t‐test or Wilcoxon–Mann–Whitney tests were applied to compare the data on LPS and LTA with clinical and radiographic features. The associations between the clinical and radiographic features and the bacterial species were analysed using the Fisher's exact test. A significance level of 5% was adopted. Results: Bacterial DNA, LPS and LTA were detected in all samples. Parvimonas micra was the most commonly detected species in all groups, followed by Enterococcus faecalis, Fusobacterium nucleatum and Porphyromonas endodontalis . The type of endodontic treatment, whether a primary root canal treatment or retreatment, was not associated with the presence of any bacterial species in periapical lesions. The levels of LPS and LTA in periapical lesions of root filled teeth were not significantly different from those that had been retreated. Associations between the levels of LPS and LTA with clinical signs and symptoms were found. No association was found between specific bacteria and clinical features. Conclusion: Periapical lesions associated with teeth after primary root canal treatment and retreatment had similar polymicrobial composition. The levels of LPS and LTA in periapical lesions associated with teeth after primary root canal treatment and retreatment were similar, and both were associated with the same symptomatology.